Proceedings of the 2007 ACM SIGMIS CPR Conference on Computer Personnel Research: The Global Information Technology Workforce 2007
DOI: 10.1145/1235000.1235004
|View full text |Cite
|
Sign up to set email alerts
|

Best practice for grooming critical mid-level roles

Abstract: The motivation for the study is to examine the effects of several trends on the IT workforce. The purpose of the study is to understand several key mid-level roles in IT client organizations, which are gaining importance for organizations as they employ alternative sourcing arrangements. Mid-level positions, such as project manager, senior system analyst, relationship manager and system architect, continue to be in demand in the organizations we study. Organizations use these roles to design solutions and coor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…IT professionals must manage their own development using mechanisms such as job rotation, on-going training, and continuing education [10].…”
Section: The Case For a Varied Set Of Skillsmentioning
confidence: 99%
“…IT professionals must manage their own development using mechanisms such as job rotation, on-going training, and continuing education [10].…”
Section: The Case For a Varied Set Of Skillsmentioning
confidence: 99%
“…One of the programmers interviewed had moved through several groups within his company to gain skills in different technologies, pursuing what Schein (1990) calls a circumferential career path. Gallagher et al (2007) also find support for this phenomenon: "Responding to why they might leave or what caused turnover in these positions, the lack of a challenge was the overwhelming response. Several stated that if they had to do the same work for an extended period, they would rather change jobs or even work for another firm" (p.17).…”
Section: Career Pathmentioning
confidence: 96%
“…(Gallagher, Kaiser, Frampton and Gallagher 2007, p.17) Further confusion for people considering a software career relates to roles. There are no clear role definitions in the software world (Belbin 2000;Shaw 2000;Gallagher et al 2007;Downey 2009). Two people with the same job title could have widely differing responsibilities.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively there is increasing demand for mid-level IT workers in positions such as project managers, systems analysts, and relationship managers (Gallagher et al, 2007;Zwieg et al, 2006), three key roles identified as vital to the IT department (Overby, 2007) according to an article in CIO Magazine. However, due to their lack of work experience, professionals may not be suited for the roles and responsibilities of these more advanced mid-level positions and what knowledge, skills and abilities (KSAs) are required in order to attain and succeed in such a role.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Organizations struggle to define and outline IT career ladders for their employees. This is especially problematic if they no longer hire into traditional entry-level positions (Gallagher et al, 2007). One respondent explained (in our exploratory research described shortly), "I can buy skills in the application development world offshore…but my architects, I want to develop in house… [but then] I'm taking a large part of the feeder group out…I'm going to have a problem here."…”
Section: Background and Literature Reviewmentioning
confidence: 99%